Basic Research Capabilities Improvement Through Training of Supporting Research Tools - Destria Kurnianti; Hera Khairunnisa; Dwi Handarini; Marsofiyati; Muhammad Yusuf; Choirul Anwar; Karuniana Dianta; Mundhiharno; Mohd Hasimi Yaacob; Anggi Novia Fitriani (PERDULI: Jurnal Pengabdian kepada Masyarakat, 2024)
Research is an important activity for Higher Education. Higher Education always encourages its lecturers and students to conduct useful research for the society. The importance of improving the quality of basic research skills for students is the background of this activity. This Community Service activity aims to provide insight and understanding related to the use of research supporting tools such as VOSviewer, Publish or Perish, and Mendeley. This activity involved students from the Faculty of Economics Universitas Musi Rawas and the Faculty of Economics and Business, Universitas Muhammadiyah Prof. Dr. HAMKA as the participant. The method of organizing this activity is a classical approach such as demonstrations from speakers, and interactive discussions with participants. The conclusion of the activity is that participants' insights and understanding of VOSviewer, Publish or Perish, and Mendeley have increased. These conclusions were obtained through questionnaires distributed to participants before and after the activity. Keywords: Research, Community Service, VOSviewer, Publish or Perish, and Mendeley.